Expert client service delivery practices among adolescents living with HIV in Eswatini: A thematic analysis. (January 2022) - Ahmed, Charisse V.; Weissinger, Guy; Teitelman, Anne; Sabelo Dlamini, Ndumiso; Patience Dlamini, Nontsikelelo; Cebsile Dlamini, Thuthukile; Nkambule, Angel; Nkambule, Siphesihle; Brawner, Bridgette M.; Calnan, Marianne
Highlights: Expert client services improve HIV treatment adherence for Swazi adolescents. Expert clients provide developmentally appropriate services to Swazi adolescents. Expert clients manage issues of HIV disclosure among Swazi adolescents. Expert clients need support to promote adolescent sexual and reproductive health. Abstract: In Eswatini (formerly known as Swaziland), expert clients are HIV-positive lay health workers known to provide psychosocial support to their seropositive peers. However, the existing literature does not specify the service delivery techniques used by expert clients to promote medication adherence and treatment retention among adolescents living with HIV. Therefore, our qualitative study sought to explore expert client service provision for adolescents with HIV using Braun and Clarke's (2006) method of thematic analysis. We recruited 32 adolescents living with HIV to participate in focus groups as well as 20 expert clients and 12 key informants to participate in semi-structured interviews. We found that the adolescent service delivery techniques used by expert clients include 1) navigating issues of disclosure, 2) serving as role models, 3) tailoring speech and behavior, 4) building rapport and trust, 5) resolving adherence challenges, and 6) promoting resilience and independence. To our knowledge, our study is the first to illuminate the specific roles that expert clients play in promoting the health of adolescents living with HIV in Eswatini. Future research should explore strategies and resources necessary to support the work of expert clients in an adolescent context, especially with regard to disclosure challenges faced by adolescents and their caregivers as well as adolescent sexual and reproductive health needs.